Innovations in architecture and the impact of architects´ mobility on their application: the case of the new building of the Slovak National Theatre in Bratislava - Katarína Haberlandová; Laura Krišteková (Historický Časopis, 2023)
The study deals with the topic of initiation, development and implementation of the idea of constructing a new theater building in Bratislava. Although the idea to build a modern Slovak National Theater has its origin already in the interwar period, it was only realized in 2007, when the new theater building was opened. The long process of the preparation and construction of the theater was primarily determined by the complexity of this task, which could not be solved satisfactorily for decades. The competition for the design of the theater was preceded by an urban competition for its location, where a decision was made between seven variants spread across the city. Later, the conditions of the architectural competition for the building (1979) were formed, which made extremely high demands on the architects, because the main goal was to create an innovative architecture not only from the formal, but also a technological point of view. In addition, another important goal was to combine spaces for drama and opera in one building, which was a unique solution at that time. Using the example of the genesis of thinking about the new modern theater building as one of the national cultural institutions, the study identifies and describes the key moments of the post-war architectural discourse. The aim of the text is to expand urban and historical-architectural research with new topics, especially focused on the reflections of the foreign architectural scene in relation to innovations in the architecture. It is also so far the most detailed analysis of the crystallazation of the designs of the new Slovak National Theater, closely linked to the wider context of post-war buildings intended for culture purposes in Slovakia, which are becoming national cultural heritage today.